SIMULASI BISNIS MINI: EDUKASI AKUNTANSI PRAKTIS MELALUI PERMAINAN DAN PROYEK USAHA ANAK PANTI - Deva Rani Kurniawan; Lisa Anitasari; Septy Annisa Nursaputri; Siti Herdalas Herlina (Jurnal Abdi Citra, 2026)
The practical accounting education activity for children at the Amanah Orphanage, conducted through games and mini business projects, aims to provide knowledge and understanding related to how children record their income and expenses, teach them how to conduct small-scale sales, and instill discipline in financial management to enhance their future well-being. The target of this mini business simulation education is the children of the Amanah Orphanage. This educational activity is carried out by providing theoretical presentations related to buying and selling, Q&A sessions, ice breakers, and giving the children the opportunity to practice directly by selling bottled water as a learning tool. The activity is monitored through cooperation between the Head of the Foundation and the orphanage management. The results of the activity show that the children were enthusiastic and capable of understanding the basics of accounting through simple practice. It is hoped that the results of this community service initiative can foster a habit of trading among the next generation of young Indonesians, which can ultimately contribute to the nation and the state, and is expected to cultivate an interest in entrepreneurship and financial literacy from an early age as a provision for future independence.